Actividades lúdicas en el desarrollo de la pre Matemática en los niños de Educación Inicial en el centro de Educación Inicial Semillitas “Cesar Francisco Naranjo Rumazo” en el año lectivo 2022-2023. - Casa Tapia, Shirley Adamary (2023)
This research was based on the fact that most teachers need to use playful activities to develop pre-mathematics at the preschool level, making their classes unattractive and causing disinterest in learning in children, leaving them with learning gaps; the research aimed to diagnose the development of pre-mathematics through play activities in early education. The population to be studied were students between four and five years of age in sub-level two parallel "E," so the qualitative approach was taken into account, with the methods of bibliographic research, inductive, taking into account the technique of observation and as an instrument a checklist for the children and an observation sheet for the teachers of the "Semillitas" early education center, the study aimed to identify the application of play activities in the development of pre-mathematics at the preschool level. Play activities in developing logical-mathematical thinking are beneficial and essential, as they allow children to develop their skills and abilities differently, learning under a play and work methodology in the classroom.